The Anatomical Relationships in the Space of Retzius for Penile Implants: An MRI Analysis. Issue 11 (18th September 2021) - Punjani, Nahid; Monteiro, Leonardo; Sullivan, John F.; Flores, Jose; Ortega, Yanira; Matsushita, Kazuhito; Choi, Judy M.; Elterman, Dean; Akin, Oguz; Nelson, Christian J.; Sandhu, Jaspreet S.; Mulhall, John P.
ABSTRACT: Background: The 3-piece inflatable penile prosthesis includes an easy-to-use pump and fluid filled reservoir which is placed in either the space of Retzius (SOR) or in an alternative ectopic location. Reservoir placement in the SOR is a blind procedure despite the SOR being surrounded by many critical structures. To date only a handful of cadaveric studies have described the relevant anatomy. Aim: To use magnetic resonance imaging (MRI) as an in-vivo model to study relevant retropubic anatomy critical for SOR reservoir placement. Methods: The study population included men with elevated prostate specific antigen or biopsy proven prostate cancer who (i) underwent pelvic MRI, (ii) without prior pelvic or inguinal surgery, and (iii) without pelvic radiation therapy. All MRIs were completed with a 3-Tesla scanner and endorectal coil. Both T1 and T2 weighted images were captured in both axial and sagittal planes. All images were reviewed by 2 independent reviewers under the supervision of a dedicated body MRI radiologist. Bladder volume was calculated using an ellipsoid formula. Outcomes: Relevant measurements included (i) the distance between the external inguinal ring (EIR) at the level of the pubic tubercle to the external iliac vein (EIV), (ii) the distance from the EIR at the pubic tubercle to the bladder (accounting for bladder volume) and (iii) the distance from the midline pubic symphysis to the bladder (accounting for bladder volume). Pearson correlation was used to determine correlated measurements. RESULTS: A total of 24 patients were included. Median participant age was 63 years (interquartile range, 59-66). The mean EIR-EIV distance was 3.0 ± 0.4 cm, the mean EIR-bladder distance was 1.8 ± 1.0 cm and the mean distance from the superior pubic symphysis to bladder was 0.9 ± 0.3 cm. There was a weak correlation between bladder volume and distance between the EIR and bladder ( r = -0.30, P = .16). Clinical Implications: The use of MRI as an in-vivo model is a high-fidelity tool to study real time unaltered anatomy and allows for surgical preparation, diagnosis of anatomic variants and acts as a valuable teaching tool. Strengths & Limitations: This is the first in-vivo model to report relevant retropubic anatomy in penile implant surgery. Our study is limited by sample size and inclusion of participants with no history of prior pelvic intervention. CONCLUSION: We demonstrate the utility of MRI as an in-vivo model, as opposed to cadaveric models, for the understanding of relevant retropubic anatomy for implant surgeons.